Penguatan Kemampuan Hafalan Surat Pendek Menggunakan Metode Al-Qasim dan Tikrar pada Pelajar Migran di Malaysia - Lu'lu' Hilyatuz Zakiyah; Edi Nurhidin; Fitta Nurisma Riswandi; Makhfud Makhfud (Al Khidma: Jurnal Pengabdian Masyarakat, 2026)
Indonesian migrant Muslim students in Malaysia face several challenges in accessing religious education, such as a lack of Quran reading and memorization of short surahs. To address these issues, this community service program aims to improve memorization of short surahs among Indonesian migrant children in Malaysia by applying the Al-Qasim and Tikrar methods. This community service program uses the ABCD (Asset-Based Community Development) method, which focuses on developing existing assets and potential. The stages consist of observation, method introduction, memorization reinforcement, and evaluation related to the development of the migrant children's memorization. The results of this community service program show three findings. First, there is an increase in fluency in reading the Quran, as demonstrated by their ability to practice reading it according to the makharijul letters. Second, their ability to memorize short surahs also increases, indicated by their fluency in reading and the duration of memorization. Third, they have greater motivation to learn and greater self-confidence, which deepen their ability to learn the Quran.